An Exploratory Study of the Participation Stages in Trang Communities to Enhance Tourism Attractiveness - Wongsuwatt, Sippavit; Thaothampitak, Wipada; Jantamaneechot, Tippawan; Prommas, Pansa (Journal of Community Development Research (Humanities and Social Sciences); Vol 17 No 4 (2024): October - December 2024DO - 10.14456/jcdr-hs.2024.25, 2024)
A key driving force of Thailand’s economy is the tourism and hospitality industry, in general and locally, across many varied tourism resource bases. This is especially true of community units which are ubiquitously recognized as a key element of tourism that can be utilized to improve a community’s economic status. This study aimed to explore the participation stages of the Trang community and examine the influence of community participation on tourism attractiveness. Quantitative research methods were used. We recruited 388 participants using purposive sampling in this study. The sample size consisted of Trang people over 18 years old, who had been living in the community for at least one year, and attended at least one activity provided by the community, gathered by face-to-face questionnaires. The Ordinary Least Square (OLS) was employed to test a statistical model to determine the influences of community participation on tourism attractiveness. Results revealed three explored participation stages in the context of the Trang community. In addition, the findings exhibited the positive influences of all three stages of community participation on tourism attractiveness. Community participation is an integral component of tourism development to enhance the tourism attractiveness of a community. Yet, to date, few studies have been conducted to determine community participation’s influence on tourism in the context of Trang’s communities, which have shown to be key factors for enhancing tourism in other contexts. Thus, this research intends to eliminate this gap in academic knowledge and present useful discussions of the related implications based on the findings. Keywords: Community Participation, Trang Province, Tourism Attractiveness, Exploratory Study